Epidemiology and outcome of suspected inhalational burn injury in a Ghanaian tertiary hospital - Pius Agbenorku; Manolo Agbenorku; Jonathan Bayuo; Nana Yaa Odamea Asare (Elsevier, 2019)
Background: Approximately 6-20% of burned patients have a concurrent inhalational injury, and the combination of inhalational injury and cutaneous injury may increase the patient's risk for increased mortality. Objective: To assess the epidemiology and outcomes of burns associated inhalational injury in a Ghanaian tertiary facility. Methodology: A retrospective approach was utilised, from January 2010 to December 2016. Patients' folders were retrieved to confirm data obtained. Descriptive statistics were generated to understand the characteristics of the study participants. Results: Out of 616 patients admitted at our Burns Intensive Care Unit with cutaneous burns, 59 (9.57%) of them had concurrent inhalational injury. Fifty-four out of the fifty-nine patients died with percentage mortality of 91.53%. More males were admitted with inhalational injury (81.40%) as compared to females. Majority of patients with inhalational injury were within the ages of 21-40 years (n = 21). The total burned surface areas were within 10%-50% with most patients within the limits of 41%-50%. Mean cutaneous burn size was obtained as 41.29% (SD = 21.7). Most patients spent 5-15 days (n = 32) on admission with mean of 11.91 days. Conclusion: Mortality resulting from concurrent burns and inhalational injury is very high. Various advanced techniques and equipment need to be made available for excellent patient management. Keywords: Inhalational injury, Burns, Mortality, Admission